Effects of cervical collar on entrance surface dose, exit surface dose and image quality in plain radiography: a phantom study - Adnan, Nadhratul Wardah; Sayed, Inayatullah Shah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
Introduction: Trauma patients presented to emergency department usually come with spinal immobilization device as a precaution and initial pre-management care by emergency medical personnel. These types of patients are at higher risk for suspected cervical fractures and internal injuries. The use of cervical collar raises some issues on radiation dose to the patient and image quality. Therefore, the use of cervical collar in routine trauma patients is questioned by researchers. The purpose of this paper was to investigate the effect of cervical collar on entrance surface dose, exit surface dose and image quality. Methods: Siemens Multix Top CR System and Kyoto Kagaku PBU-50 Body Phantom was used. The phantom was positioned supine on the table couch and was exposed with and without cervical collar. An Anteroposterior (AP) Axial cervical projection was performed and the phantom was also exposed with and without Automatic Exposure Control (AEC) to study the effects on radiation dose and image quality. The dose reading was recorded in all exposures and compared. Images obtained were analyzed for Signal to Noise Ratio (SNR). Results: Lower entrance dose was recorded with cervical collar when the AEC was disabled during the exposure and the results were vice versa when the AEC was enabled. Higher exit dose was calculated when cervical collar was applied to the phantom. Greater signal to noise ratio (SNR) was observed with cervical collar. Conclusions: This study concluded that cervical collar adds to exit dose and without any impact on image quality. The entrance surface dose recorded with cervical collar and AEC disabled was lower compared to when it was removed. The entrance dose recorded with collar and the AEC enabled was higher compared to when it was removed.